Legal and Regulatory Aspects of Compounding Radiopharmaceutical Medicinal Products in Healthcare Organizations of the Republic of Kazakhstan - A. N. Gurin; G. E. Kodina; Y. T. Chakrova; I. K. Tleulessova; N. V. Pyatigorskaya; M. G. Grinin (Regulatory Research and Medicine Evaluation, 2026)
INTRODUCTION. The current regulatory framework of the Republic of Kazakhstan does not provide for a special legal regime governing the compounding and circulation of radiopharmaceutical medicinal products (RMPs) in healthcare organizations. As a result, the requirements of legislation regulating pharmacy operations, pharmaceutical manufacturing, and medical activities apply to this sphere simultaneously, creating legal uncertainty and difficulties in the application of legislation. This necessitates the development of a differentiated approach to the legal regulation of this activity. AIM . To analyze the legal and regulatory framework for in-hospital compounding of radiopharmaceutical medicinal products in the Republic of Kazakhstan and to assess the compliance of current requirements with the practical conditions of healthcare organizations' activities. DISCUSSION. Pharmacy compounding of RMPs in the Republic of Kazakhstan is regulated by several normative legal acts belonging to different regulatory regimes: pharmaceutical, medical, and radiation safety. The Code “On Public Health and the Healthcare System” exempts pharmacy‑compounded radiopharmaceutical medicinal products from state registration; however, it does not establish a specialized regulatory model for this category of products. The Good Pharmacy Practice (GPP) standard is primarily oriented toward non-radioactive medicinal products and does not fully account for the specific characteristics of radiopharmaceutical medicinal products. The Standard for the Organization of Medical Care in the Field of Nuclear Medicine introduces requirements that are close to an industrial manufacturing model, including infrastructure elements and quality systems comparable to Good Manufacturing Practice (GMP) principles. While such an approach is reasonable for large-scale production facilities, it appears excessive for healthcare organizations that prepare RMPs solely for their own clinical use. The analysis revealed the need to develop a dedicated set of regulatory legal acts based on a risk-oriented approach, taking into account the dual nature of RMPs as both medicinal products and sources of ionizing radiation. CONCLUSIONS. To achieve a balance between the accessibility of radiopharmaceutical technologies and the assurance of quality and safety of RMPs, it is advisable to establish a clear regulatory differentiation between the in-hospital compounding of RMPs (including their clinical use as methods of personalized medicine) and the industrial production of RMPs subject to state registration. Furthermore, it is necessary to develop a risk-based regulatory model for the preparation of medicinal products, tailored to the practical conditions of healthcare organizations' activities in the Republic of Kazakhstan. The implementation of these approaches will reduce regulatory risks, enhance legal certainty, and create a sustainable foundation for the further development of nuclear medicine in the Republic of Kazakhstan.